2021
DOI: 10.1617/s11527-021-01721-x
|View full text |Cite
|
Sign up to set email alerts
|

Torsion-shear behaviour at the interfaces of rigid interlocking blocks in masonry assemblages: experimental investigation and analytical approaches

Abstract: Increasing interest has recently been devoted to interlocking blocks/interfaces capable to enhance the sliding resistance of masonry joints to external forces. In this framework, this paper deals with the assessment of the torsion-shear capacity of the contact interface between the lock and the main body of an interlocking block, assumed to have a cohesive behaviour. The interlocking block is a rigid unit which, on its faces, have square cuboidal locks keeping the adjacent/overlapped blocks together and preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…For the sake of consistency with the experimental torsion-shear tests carried out by the authors with others [27,28], the dimensions shown in Figure 2 are defined for stacked blocks with an interlocking joint. Two samples are presented in this figure, one with three and one with five locks.…”
Section: Multi-lock Interface Problemmentioning
confidence: 96%
See 4 more Smart Citations
“…For the sake of consistency with the experimental torsion-shear tests carried out by the authors with others [27,28], the dimensions shown in Figure 2 are defined for stacked blocks with an interlocking joint. Two samples are presented in this figure, one with three and one with five locks.…”
Section: Multi-lock Interface Problemmentioning
confidence: 96%
“…The results obtained using the novel SiDMACIB model are then compared to the results obtained using the well-established DE analysis (3DEC 7.0, free version [30]), and some proposals to adjust or better calibrate the former formulation are finally presented. 3DEC has been chosen as a reliable candidate to carry out this validation because the experimental tests for single locks presented in [27,28] showed strong agreement with the results obtained by 3DEC.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations